TACTICS FOR DYNAMIC DATA CLEANSING AND DATA PROFILING USING DIMENSIONS FOR DATA QUALITY ASSESSMENT - Ghouse Mohiddin, A; Ramakrishna, S (International Journal of Computer Sciences and Engineering, 2025)
We classify data quality problems that are directed by data cleaning and provide an overview of the principal Solution approaches.Data cleansing is particularly needed when integrating heterogeneous data sources and Should be directed together with schema-related data transformations. We also discuss current tool support for data cleanup. Data profiling is a specific form of data analysis customer data to detect and characterize important features of data sets. Data Analysis offers a delineation of data structure, content, rules and relationships by using statistical methodologies to deliver a lot of standard characteristics about data -data types, field lengths and cardinality of columns, granularity, value sets, format patterns, content patterns, implied rules, and cross-column and cross-file data relationships and cardinality of those relationships. Data deduplication has been advocated as a promising and effective technique to save the digital space by removing the duplicated data from the data centres or clouds. Data deduplication is a process of identifying the redundancy in data and then removing it. The resulting unique data/Consolidate data into single format using data cleansing and Data standardization. Use scorecards to measure data quality progress and shared URL link to the stakeholder.